A 3-D view on the mechanisms of short fatigue cracks interacting with grain boundaries - Schaef, W.; Marx, M.; Vehoff, H.; Heckl, A.; Randelzhofer, Peter (Acta Materialia, 2011)
Short fatigue cracks propagate with a fluctuating crack growth rate while interacting with microstructural barriers. Although some models of the interaction exist, it is not clear what determines the strength of the resistance of a grain boundary to crack propagation. Therefore we developed a method for artificial crack initiation which uses a focused ion beam (FIB) to nucleate cracks crystallographically on single slip planes identical to natural stage I cracks. The crack parameters as well as the grain boundary parameters can be varied independently for systematic experiments. For the first time the crack path through a grain boundary is shown in 3-D by FIB tomography. This enables the interaction between microcracks and grain boundaries to be observed in 3-D with a high spatial resolution. It is not only the inclination angle between the active slip systems, but also the inclination angle of the grain boundary, which determines the strength of these microstructural barriers. (c) 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Fatigue crack growth; Short cracks; Grain boundaries; Crack arrest; FIB tomography

ATI718PLUS® - New nickel based disc alloy and its capability - Huenert, Daniela; Pröbstle, Martin; Casanova, Ana; Schlütter, Regina; Krakow, Robert; Büscher, M.; Randelzhofer, Peter; Evans, A.; Löhnert, Katja; Witulski, T.; Neumeier, Steffen; Rae, Catherine M. F. (Superalloys 2016: Proceedings of the 13th Intenational Symposium of Superalloys, 2016)
Two extreme microstructural variants of alloy ATI718PLUS® were investigated regarding their tensile strength, creep resistance, long-term stability, oxidation and crack growth properties. The variants were produced by supersolvus and subsolvus forging procedures. A subsolvus forging produces fine-grained microstructure with aligned blocky secondary η-phase. The supersolvus forging generated a coarser grain size with improved creep performance and non-aligned lamellar η-phase. The oxidation behavior has been characterized showing superior performance of ATI718PLUS® relative to alloy 718 and 720LI. The results have been used to design optimized microstructures balancing the properties required for critical rotating parts. The analysis of several test conditions show, that key properties can be altered over a wide rang
Keywords: ATI718Plus® alloy; Creep; FCG; Long term stability; Oxidation; Tensile

Bohrhaken-Material-Korrosion - Randelzhofer, Peter (bergundsteigen, 2019)

Characterization of magnesium alloys for semi solid processing - Kramer, Markus; Jenning, Ralf; Lohmüller, Andreas; Hilbinger, Rolf Michael; Randelzhofer, Peter; Singer, Robert (Magnesium: 8th International Conference on Magnesium Alloys and their Applications, 2009)

Crack formation during solidification - Blackford, Jane; Randelzhofer, Peter; Singer, Robert (Erstarrung metallischer Schmelzen in Forschung und Gießereipraxis, 1999)

Creation and characterization of specimen with pores for fatigue tests and castings process simulation - Hilbinger, Rolf Michael; Gerth, Stefan; Randelzhofer, Peter (Materialwissenschaft und Werkstofftechnik, 2017)
A large number of specimens has been created and investigated for fatigue tests and the numerical simulation of porosity formation in castings. The specimens are made out of the alloy AlSi7Mg0.3, the porosity has been characterized by means of computer tomography. The obtained results are put into relation with production conditions, with emphasis on melt hydrogen content. Form and amount of porosity is investigated in conjunction with melt hydrogen content and the transition between solidification and gas porosity is documented. The evolution of pores of different size is scrutinized in detail.
Keywords: Aluminium; Casting; Computer tomography; Hydrogen content; Porosity

Design and Characterization of a Novel NiAl–(Cr,Mo) Eutectic Alloy - Titz, Katharina; Vollhüter, Jan; Randelzhofer, Peter; Neumeier, Steffen; Göken, Mathias; Wahlmann, Benjamin; Körner, Carolin (Advanced Engineering Materials, 2024)
To enhance the mechanical properties of NiAl–(Cr,Mo) in situ composites for high-temperature structural use, achieving a regular eutectic microstructure is crucial. A novel alloy with a composition of Ni30.6Al36Cr31.4Mo2 is developed that exhibits a significantly reduced solidification interval compared to well-studied alloys such as Ni33Al33Cr28Mo6. This advancement results from using the in-house developed alloy design tool PyMultOpt and Calculation of Phase Diagrams analysis to minimize the solidification interval. The refined alloy demonstrates a theoretical solidification interval of 0 K. These results are verified with differential scanning calorimetry measurements at different heating rates for the new alloy and compared with the established alloy Ni33Al33Cr28Mo6. The small solidification interval leads to a uniform eutectic microstructure consisting of a (Cr,Mo) phase embedded in the NiAl matrix without primary NiAl dendrites present. This indicates that deviating from the stoichiometric NiAl composition results in a significantly lower solidification interval and thus in an actual eutectic composition of the NiAl–(Cr,Mo) system.
CRIS-Team Scopus Importer:2024-04-05
Keywords: alloy development; eutectics; intermetallics; nickel aluminides

Effect of Zr, Cr and Sc on the Al–Mg–Si–Mn high-pressure die casting alloys - Prach, Olena; Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin; Durst, Karsten (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
New aluminium Al5Mg2SiMn casting alloys with Sc, Cr, Zr addition have been developed. The effect of the alloying elements in amount of 0.1 and 0.2 wt.% on the microstructure and mechanical properties of the Al5Mg2SiMn casting alloy produced by the HPDC was investigated. The microstructure was observed by means of the scanning electron microscopy and electron probe microanalysis. The hardness of the aforementioned alloys was determined by Brinell and nanoindentation testing. The microstructure of the HPDC aluminium alloys consists of primarily α-Al phase, the α-Al15(Mn,Fe)3Si2 intermetallics and Al-Mg2Si eutectic cells. Coarse Al7Cr as well as Al3Zr intermetallic phases in the alloys with Cr and Zr addition were observed. The most significant improvement in the mechanical properties was achieved in the alloys with Sc addition. Alloying with 0.2 wt.% of Sc exhibits the best combination of strength and ductility with a yield strength of 196 MPa, an ultimate tensile strength of 341 MPa and 10 % of elongation in the as-cast condition. Alloys with Cr and Zr additions present the similar properties in terms of hardness compared to the alloys with Sc addition and the similar tensile properties comparable to the AlMg5Si2Mn (commercially known as “Magsimal-59”) base alloy.
Keywords: Al-alloys; Chromium; Zirconium; Scandium; Microstructure; Mechanical properties

Formation kinetics and phase stability of in-situ Al3Ti particles in aluminium casting alloys with varying Si content - Himmler, David; Randelzhofer, Peter; Körner, Carolin (Results in Materials, 2020)
The intermetallic phase Al3Ti is a promising candidate to increase the stiffness of aluminium casting alloys due to its high Young’s modulus. The phase is formed by the in-situ reaction between solid titanium particles and the liquid aluminium melt. High-shear mixing technology is used to peel off the reaction layer on the surface of the Ti particles and distribute the Al3Ti particles homogeneously in the melt. This work investigates the influence of the Si content of three different aluminium casting alloys on the in-situ reaction. Additionally, the influence of the initial titanium powder particle size and the process temperature on the formation kinetics are investigate
Keywords: aluminium alloys; high-shear technology; Al3Ti phase formation

Functional Property Improvement Of The HPDC Alloy AlSi9Cu3Fe Through Sr And Heat Treatment - Feyer, Felix; Hsiung, Ming-Hao; Randelzhofer, Peter; Körner, Carolin (6th International Conference on Light Materials - LightMat 2025, 2025)

Heat treatment of high-pressure die casting Al-Mg-Si-Mn-Zn alloys - Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin (Journal of Alloys and Compounds, 2021)
The microstructure and mechanical properties of Al-5.7Mg-2.6Si-0.7Mn-xZn high-pressure die casting alloys after heat treatment have been investigated. The microstructure was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The hardness was determined by Brinell and Vickers testing. The effects of T5 (artificial ageing from the as-cast state) and full T6 heat treatment modes on the alloys with different Zn content (0.6…5 wt.%) on the microstructure and mechanical properties were investigated. The solution treatment changes the microstructure of the studied alloys. The T-AlMgZn phase dissolves into the α-Al phase during solution treatment at temperatures higher than 375ºC. Artificial ageing at 125-225ºC doesn’t lead to any changes in the microstructure of alloys, however, leads to the formation of several types of Zn-containing precipitates in the α-Al. The optimal temperature for artificial ageing from the as-cast state as well as after solution treatment is in the range 125-175ºC for 2-5 h. It was found that the most noticeable changes in the mechanical properties were achieved in the alloys with 1.2-1.8 wt.% Zn. It was found that these changes are associated with Zn distribution, the morphology of the phases and the formation of nano-sized precipitates in α-Al solid solutio
Keywords: Al-Mg-Si-Mn-Zn alloys; heat treatment; precipitation strengthening; mechanical properties

Heat treatment of the new high-strength high-ductility Al–Mg–Si–Mn alloys with Sc, Zr and Cr additions - Trudonoshyn, Oleksandr; Prach, Olena; Randelzhofer, Peter; Durst, Karsten; Körner, Carolin (Materialia, 2020)
Heat treatment of alloys of the Al–Mg–Si system essentially affects the age-hardening response and, accordingly, their final mechanical properties. However, the specific Mg/Si ratio in casting alloys makes age-hardening by heat treatment negligible. To improve the age-hardening response, the alloys were alloyed with Sc, Cr, Zr, and two types of heat treatment were applied: full T6 (solution treatment (ST), quenching, and artificial aging (AA)); and T5 with AA from the as-cast state. The microstructure after different heat treatment modes was observed by means of SEM and TEM. It was established that the main structural components that affect the mechanical properties of alloys after heat treatment are nanoscale precipitates and a coarse Al 7 Cr and Al 3 Zr intermetallic phases in the Cr- and Zr-containing alloys. The highest impact in terms of tensile properties was achieved in the Sc-containing alloys after T5 at 325 °C. Alloys with 0.2 wt% Sc exhibit the highest strength after T5 from as-cast state at 325 °C (up to 380 MPa) and highest elongation (up to 20%) after full T6 (ST 520 °C and AA 325 °C). <br
Keywords: Al–Mg–Si alloys; Heat treatment; Mechanical properties; Scandium addition

Improvement of the high-pressure die casting alloy Al-5.7Mg-2.6Si-0.7Mn with Zn addition - Trudonoshyn, Oleksandr; Rehm, Sebastian; Randelzhofer, Peter; Körner, Carolin (Materials Characterization, 2019)
The microstructure and mechanical properties of the high-pressure die casting alloys Al-5.7Mg-2.6Si-0.7Mn-xZn in as-cast condition have been investigated. The microstructure was studied by scanning electron microscopy (SEM), electron probe microanalysis (EPMA) and transmission electron microscopy (TEM). Intermetallic particles and volume fractions were measured using partly automated image analysis in the software Fiji/Imagej. Results of the microstructure analysis were compared with Thermo-Calc calculations. The hardness was determined by Brinell (HB) and local properties were determined by Vickers (HV0.01) testing. The ultimate tensile strength (UTS), yield strength (YS) and elongation were performed by conventional tensile tests at room temperature. The microstructure of the studied alloys consists primarily of α-Al phase, the α-AlFeMnSi intermetallics, Al–Mg2Si eutectic cells. Addition of Zn leads to the formation in the structure T-AlMgZn phase. The higher Zn content in the alloy the higher volume fraction of T-AlMgZn phase. The increasing of Zn content in the alloy leads to its increasing in α-Al accordingly. The addition of 1.2–1.8 wt% Zn to the base alloy caused the most significant changes in mechanical properties. Alloying up to 1.2 wt% Zn shows the improvement of strength and hardness while the elongation value remains at the same level as in the base alloy. Alloying with 1.8 wt% Zn shows the highest level of strength (380 MPa of UTS) but the level of elongation decreased. With further increase of Zn concentration the YS and HB continued their growth (up to 270 MPa of YS and 120 HB) whilst elongation and UTS decreased.
Keywords: Al-Mg-Si alloys; Age hardening; Precipitates; Microstructure; Mechanical properties

Increasing the conductivity of aluminium high-pressure die casting alloy AlSi9Cu3Fe (226D) by Sr modification of eutectic and intermetallic phases - Feyer, Felix; Weigand, Michael; Randelzhofer, Peter; Körner, Carolin (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2025)
High-pressure die casting alloys are currently optimized to have an excellent castability and to fulfil the mechanical properties of the demanded parts. In general the conductivity of these alloys decreases from the efforts to improve the mechanical properties and the castability. Although new components in the mobility and communication sector demand alloys with improved conductivity. Focus of the work is the evaluation of influence of modification on the conductivity and mechanical properties of high-pressure die casting alloy AlSi9Cu3Fe. A new Cu-die design with vacuum assistance which mimics the microstructure of high-pressure die castings on lab scale for high throughput investigation was used. The combination of modification of the Si phase and intermetallic phases morphology and distribution collectively influences the properties of the alloy. The extent of modification is connected to the level of alloying elements and Sr content present. The conductivity is increased by more than 10
Keywords: Al alloys; Si modification; Conductivity; Hardness; High throughput

Influence of mould filling and microstructure on electrical conductivity in aluminium high pressure die casting parts - Feyer, Felix; Randelzhofer, Peter; Körner, Carolin (Journal of Physics: Conference Series, 2025)
Aluminium high pressure die casting (HPDC) parts are widely used as structural components and housings in the mobility sector. The components possess a favourable density to strength ratio and an excellent castability in HPDC process. The ongoing change towards electric drive systems transformed casting parts and sets other standards for the properties of these parts. The functional integration of cast parts becomes more important for the new applications in the electromobility sector. Most of the new housing components include electrical components that emit heat and need cooling. Thus, heat transfer and conductivity of cast parts become a focal point in these applications. However, there is little information about how the conductivity in HPDC parts is influenced by the casting process. Furthermore, the resulting microstructure influence on the conductivity within a component is unclear. The aim of this work is to study the influence of the HPDC mould filling process onto the developing microstructure and eventually the influence on the conductivity. The analysis is based on the comparison of mould filling simulations with electrical conductivity measurements and microstructural investigations of HPDC components. The results indicate that the electrical conductivity is a function of the local microstructure within the cast part based on the mould filling.
CRIS-Team Scopus Importer:2025-08-01

In situ Al3Ti/Al composites fabricated by high shear technology: microstructure and mechanical properties - Zeng, Yan; Himmler, David; Randelzhofer, Peter; Körner, Carolin (Materials Science and Technology, 2019)
In situ Al3Ti/Al composites were produced by the reaction between Ti powder and Al melt with high shear technology. As Ti powder is starting material, it is important to investigate its size effect on the microstructure and mechanical properties of Al3Ti/Al composites. The results indicate that the necessary reaction time increases with increasing Ti particle diameter, which results in the Al3Ti phase coarsening. Particle sedimentation occurs at a short mixing time applying large Ti powder. Due to the presence of stiff Al3Ti particles, Young's modulus increases with particle volume fraction and fit well with the predicted values from the Halpin–Tsai equation. Moreover, together with grain refinement, these Al3Ti particles with a homogeneous distribution also lead to an increase in tensile strength.
Keywords: Aluminium matrix composites; high shear technology; intermetallic Al3Ti; Ti powder size

In-situ Al3Ti particle reinforcement for stiff aluminum die castings - Himmler, David; Randelzhofer, Peter; Körner, Carolin (Journal of Alloys and Compounds, 2022)
The intermetallic phase Al3Ti is a promising candidate to increase the stiffness of aluminium casting alloys due to its high Young’s modulus. Reinforcement particles are formed by the in-situ reaction between solid titanium particles and the liquid aluminium melt. A high-shear mixer is used to peel off the reaction layer on the surface of the Ti particles and distribute the Al3Ti particles homogeneously in the melt. This work investigates the dissolution velocity of different size fractions of Ti powder in three different aluminum casting alloys. The results were used to fabricate specimens with different volume fractions of Al3Ti particles by high pressure die casting. Microstructure characterization was performed to investigate the distribution of the Al3Ti particles within the castings. The mechanical properties were determined by tensile tests and resonant frequency analysis.
Keywords: metal matrix composites; liquid-solid reactions; mechanical properties

Microstructures and Mechanical Properties of Al3Ti/Al Composites Produced In Situ by High Shearing Technology - Zeng, Yan; Himmler, David; Randelzhofer, Peter; Körner, Carolin (Advanced Engineering Materials, 2018)
Due to its low density, high strength, and stiffness the intermetallic phase Al3Ti is a good candidate as reinforcement for Al alloys. In this work, in situ Al3Ti particle reinforced Al composites are fabricated from Ti particles and Al melt via melt stirring with a high shearing mixer. Microstructure and mechanical properties are investigated. The results indicate that, owing to the high shearing effect and intensive macroscopic flow of the melt, reinforced particles are distributed homogeneously on the microscopic and macroscopic scale. Furthermore, Al3Ti particles are proved to be effective nuclei for heterogeneous nucleation of α-Al, thus the grain size of the Al matrix is significantly decreased. As a result of the fine grains and the uniform distribution of Al3Ti particles, E-modulus, yield, and tensile strength of the composites are enhanced.

Multi-alloying effect of Sc, Zr, Cr on the Al-Mg-Si-Mn high-pressure die casting alloys - Prach, Olena; Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin; Durst, Karsten (Materials Characterization, 2020)
The alloying effects of small additions of Sc, Zr, Cr on the microstructure and mechanical properties of Al-5Mg-2Si casting alloys produced by High Pressure Die Casting (HPDC) were investigated. The microstructure of the Al-alloys consists primarily of the α-Al and Al-Mg2Si eutectic cells and the α-Al15(Mn,Fe)3Si2 intermetallic phase as well as coarse Al7Cr and Al3Zr intermetallic phases. The most significant improvement in the mechanical properties was achieved in the alloys with Sc + Cr and Sc + Zr additions. Alloying with 0.2 wt% of Sc in combination with Zr and Cr additions exhibits the best combination of strength and ductility with a yield strength of 206 MPa, an ultimate tensile strength of 353 MPa and an elongation of 10% in the as-cast condition. Alloys with Cr + Zr addition have a higher hardness and tensile strength compared to the AlMg5Si2Mn base alloy (commercially known as “Magsimal-59”) and the similar levels of yield strength and elongation. However, they have lower levels of all set of properties compared to the alloys with Sc + Cr and Sc + Zr additions, due to the presence of coarse Al7Cr sludge and Al3Zr intermetallic phase
Keywords: Al-alloys; HPDC; Chromium; Zirconium; Scandium; Mechanical properties

Oxidation Behavior of the Polycrystalline Ni-Base Superalloy VDM® Alloy 780 - Kirchmayer, Andreas; Weiser, Martin; Randelzhofer, Peter; Freund, Lisa; Gehrmann, B.; Haghighat, M. Hafez; Huenert, D.; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
VDM® Alloy 780 is a newly developed polycrystalline Ni-base superalloy with high contents of Co, Cr, and Al intended for operating temperatures up to 750 °C. The alloy is precipitation strengthened by the γ′ phase, which is analyzed by atom probe tomography. Additionally, δ and η phases are utilized for grain boundary pinning. It is shown that the δ and η phases precipitate either plate like or in a fine lamellar structure inside each other. VDM® Alloy 780 shows superior oxidation resistance in comparison with Udimet 720Li and A718Plus, as seen by a lower mass gain and thinner oxide layers at 800 °C and 900 °C. This superior behavior is analyzed in detail by TEM and STEM investigations of the oxide scales from which it is concluded that the Al/Ti ratio in these alloys plays an important role on the oxidation behavior.<br

Processing of in situ Al3Ti/Al composites by advanced high shear technology: influence of mixing speed - Zeng, Yan; Himmler, David; Randelzhofer, Peter; Körner, Carolin (International Journal of Advanced Manufacturing Technology, 2020)
High shear technology (HST) is an advanced melt stirring technology with the intensive shear effect and allows the production of particle-reinforced Al composites (PAMCs) with a homogeneous particle distribution. In the fabrication process, applying an appropriate mixing strategy to obtain the excellent microstructure and properties is crucial. In this work, Al3Ti/Al composites with different Al3Ti volume fractions were fabricated in situ by high shear technology at various mixing speeds. The effect of mixing speed on the microstructure and mechanical properties was investigated. The results show that the reaction rate and Al3Ti particle size increase with the increase of mixing speed. An intermediate mixing speed is appropriate for preparing the Al3Ti/Al composite with a homogeneous distribution of reinforcing particles and low porosity. A lower mixing speed leads to severe particle agglomerations, which deteriorates the ductility of Al3Ti/Al composites. A higher mixing speed results in high porosity within castings resulting from severe air entrainment, which significantly reduces mechanical properties. Young’s modulus improves with increasing the stiff Al3Ti particle content and matches well with the predicted results as well. Tensile and compression strength and hardness are enhanced due to generating the uniform distribution of reinforcing particles and the matrix grain refinement.
CRIS-Team Scopus Importer:2020-09-11
Keywords: High shear technology; Intermetallic Al; Mixing speed; Particle-reinforced Al matrix composites